High-entropy oxide material for negative electrode of lithium ion battery as well as preparation method and application of high-entropy oxide material
Prepared by high-entropy oxide material (Fe0.2Ni0.2Cu0.2Zn0.2Sn0.2) 3O4 and solution combustion-sol gel method, the problem of volume expansion and large-scale synthesis of lithium-ion battery negative electrode material was solved, and high specific capacity was achieved , excellent rate performance and long cycle stability simplify the preparation process and reduce costs.
Patent Information
- Application Number
- CN202411548489.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-27
AI Technical Summary
The volume expansion of the negative electrode material of traditional lithium-ion batteries seriously affects its long cycle stability, and the large-scale synthesis method is complex and unsuitable, making it difficult to achieve high specific capacity and excellent rate performance.
High entropy oxide material (Fe0.2Ni0.2Cu0.2Zn0.2Sn0.2)3O4 was used and prepared by solution combustion-sol gel method to obtain a material with uniform particle size, combined with conductive agent and coating treatment, and excellent battery negative electrode.
It achieves high specific capacity, excellent rate performance and long cycle stability, simplifies the preparation process, reduces costs, is suitable for large-scale production, and the material has a pore structure to improve the transmission channel of lithium ions.
Smart Images

Figure CN119208591A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a high entropy oxide material for negative electrodes of lithium-ion batteries, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have attracted extensive research due to their high energy density and have now achieved large-scale commercialization. The negative electrode material is an important component of lithium-ion batteries. According to the type of redox reaction, it can be divided into intercalation materials, conversion materials and alloy materials. Conversion materials have attracted widespread attention due to their higher capacity than intercalation materials and smaller volume expansion than alloy materials. However, their volume expansion still seriously affects their long-cycle stability. Traditional improvement measures generally involve structural modifications to improve their cycle stability, but such methods are not suitable for large-scale synthesis due to the complex synthesis method. Summary of the invention
[0003] In view of this, the embodiments of the present application provide a high entropy oxide material for lithium ion battery negative electrode and a preparation method and application thereof. The battery prepared with the material has high specific capacity, excellent rate performance and long cycle stability. The material has uniform and fine particle size, and the size is about 100 to 200 nm, which can effectively accelerate the transmission of ions and electrons, so that the material used for the lithium ion battery negative electrode has better capacity and rate performance; in addition, the preparation method is simple, can be scaled up for production, the operation steps are highly controllable, and can effectively overcome the defects of the existing method that is complex and not suitable for large-scale synthesis.
[0004] In a first aspect, an embodiment of the present application provides a high entropy oxide material for a negative electrode of a lithium ion battery, wherein the chemical formula of the high entropy oxide material is: (Fe 0.2 Ni 0.2 Cu 0.2 Zn 0.2 Sn 0.2 )3O4.
[0005] The second aspect of the embodiment of the present application further provides a method for preparing the above-mentioned high entropy oxide material for a negative electrode of a lithium ion battery, comprising the following steps:
[0006] Step 1, weighing an iron source, a nickel source, a copper source, a zinc source, and a tin source, dissolving them in a solvent, placing them on a magnetic stirrer and stirring to obtain a solution A;
[0007] Step 2, adding fuel to the solution A, heating and continuing to stir to obtain solution B;
[0008] Step 3, drying the solution B to obtain a gel precursor C;
[0009] Step 4: placing the gel precursor C in a muffle furnace to undergo a combustion reaction, and then keeping the temperature to obtain a high entropy oxide material precursor D;
[0010] Step 5: Cooling the high entropy oxide material precursor D in the furnace to obtain a high entropy oxide material for a negative electrode of a lithium-ion battery.
[0011] In some embodiments that may include the above embodiments, the following steps are specifically included:
[0012] Step 1, weighing an iron source, a nickel source, a copper source, a zinc source, and a tin source, and dissolving them in anhydrous ethanol, and then placing them on a magnetic stirrer and stirring for 15 minutes to obtain a solution A;
[0013] Step 2: adding a fuel in a stoichiometric ratio equal to the chemical reagent in step 1 to the solution A, placing the solution on a magnetic heating stirrer and heating at 80° C. and continuing to stir for 15 minutes to obtain a solution B;
[0014] Step 3, placing the solution B in an oven at 80° C. to dry to obtain a gel precursor C;
[0015] Step 4: placing the gel precursor C in a muffle furnace, heating it to 700-900° C. in an air atmosphere to cause a combustion reaction, and then keeping the temperature for 1 hour to obtain a high entropy oxide material precursor D;
[0016] Step 5: Cooling the high entropy oxide material precursor D in the furnace to obtain a high entropy oxide material for a negative electrode of a lithium-ion battery.
[0017] In some embodiments that may include the above embodiments, in step 1, the iron source is ferric nitrate nonahydrate; the nickel source is nickel nitrate hexahydrate; the copper source is copper nitrate trihydrate; the zinc source is zinc nitrate hexahydrate; and the tin source is tin nitrate.
[0018] In some embodiments that may include the above embodiments, in step 1, the molar ratio of the iron source, the nickel source, the copper source, the zinc source, and the tin source is 1:1:1:1:1.
[0019] In some embodiments that may include the above embodiments, in step 2, the fuel is glycine.
[0020] The third aspect of the embodiment of the present application also provides a lithium-ion battery negative electrode material, which is composed of the above-mentioned high entropy oxide material for lithium-ion battery negative electrode, conductive agent Super P and PVDF in a mass ratio of 7:2:1, ground and mixed evenly in a mortar, added with an appropriate amount of NMP and then coated on a copper foil, placed in a vacuum drying oven at 80°C for 12 hours, and rolled and cut into pieces to obtain a battery negative electrode sheet.
[0021] The fourth aspect of the embodiment of the present application further provides a lithium-ion battery, comprising the above-mentioned battery negative electrode sheet, and also comprising a battery casing, a positive electrode sheet, a separator and an electrolyte.
[0022] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0023] 1. The advantage of the high entropy oxide material for the negative electrode of a lithium-ion battery prepared by the method in the embodiment of the present application is that the combustion process will emit heat and be accompanied by the generation of a large amount of gas. Therefore, the prepared high entropy oxide material has a porous structure, which can increase the transmission channel of lithium ions;
[0024] 2. The high entropy oxide material for the negative electrode of a lithium ion battery prepared by the method in the embodiment of the present application has a uniform and fine particle size, and the size is about 100 to 200 nm, which can effectively accelerate the transmission of ions and electrons, so that the synthesized material has a better capacity and rate performance for the negative electrode of a lithium ion battery;
[0025] 3. The preparation method adopted in the present application is simple, fast and uses low-cost raw materials. First, low-cost and easily available starting raw materials are selected, and a precursor gel is obtained by combining a solution combustion-sol-gel method. After the gel is ground into powder, the precursor powder is placed in a muffle furnace and calcined to obtain a high-entropy oxide material for a negative electrode of a lithium-ion battery. The synthesis method does not require expensive raw materials, devices or complex synthesis conditions, which greatly reduces the complexity and cost of the preparation process and has practical application value.
[0026] 4. This application has prepared a negative electrode material with excellent electrochemical properties. In electrochemical tests, the battery prepared with this material exhibits higher discharge specific capacity, lower internal resistance and better cycle life, which indicates that this material has potential in lithium-ion battery applications and can meet the requirements of both performance and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0028] Figure 1 This is the XRD spectrum of the high entropy oxide material for the negative electrode of a lithium ion battery according to Example 1 of the present application;
[0029] Figure 2 This is a rate diagram of a battery prepared with a high entropy oxide material for the negative electrode of a lithium-ion battery according to Example 1 of the present application;
[0030] Figure 3 This is a long cycle diagram of a battery prepared with a high entropy oxide material for the negative electrode of a lithium-ion battery according to Example 1 of the present application;
[0031] Figure 4 This is a SEM image of the high entropy oxide material for the negative electrode of a lithium-ion battery according to Example 1 of the present application;
[0032] Figure 5 This is a locally enlarged SEM image of the high entropy oxide material for the negative electrode of a lithium-ion battery in Example 1 of the present application. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0034] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards; if there is no corresponding national standard, it is carried out according to the general international standards or the standard requirements known in the art. Unless otherwise specified, all parts are by weight and all percentages are by weight.
[0035] Unless otherwise specified, the raw materials in the examples of the present application were purchased through commercial channels, specifically as follows: ferric nitrate nonahydrate (Shanghai MacLean Biochemical Technology Co., Ltd., 99%), nickel nitrate hexahydrate (Shanghai MacLean Biochemical Technology Co., Ltd., 99%), copper nitrate trihydrate (Jiangsu Qiangsheng Functional Chemical Co., Ltd., analytical grade), zinc nitrate hexahydrate (Wuxi Zhanwang Chemical Reagent Co., Ltd., chemically pure), tin nitrate (Shanghai MacLean Biochemical Technology Co., Ltd., 99%)
[0036] Example 1
[0037] The method for preparing the high entropy oxide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0038] First, 0.404 g, 0.291 g, 0.242 g, 0.297 g, and 0.367 g (molar ratio of 1:1:1:1:1) of ferric nitrate nonahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, and tin nitrate were weighed and dissolved in 30 ml of anhydrous ethanol, and then placed on a magnetic stirrer and stirred for 15 min to obtain solution A, and then 0.075 g of glycine was added to solution A, and the solution was placed on a magnetic heating stirrer and heated at 80 ° C and continued to stir for 15 min to obtain solution B, and solution B was placed in an oven at 80 ° C for 10 h to obtain a gel precursor C, and then the gel precursor C was placed in a muffle furnace and heated to 750 ° C in an air atmosphere to cause a combustion reaction, and then kept warm for 1 h to obtain a high entropy oxide material precursor D, and the high entropy oxide material precursor D was cooled to room temperature with the furnace to obtain a high entropy oxide material (Fe 0.2 Ni 0.2 Cu 0.2 Zn 0.2 Sn 0.2 )3O4.
[0039] Example 2
[0040] The method for preparing the high entropy oxide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0041] First, 0.404 g, 0.291 g, 0.242 g, 0.297 g, and 0.367 g (molar ratio of 1:1:1:1:1) of ferric nitrate nonahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, and tin nitrate were weighed and dissolved in 30 ml of anhydrous ethanol, and then placed on a magnetic stirrer and stirred for 15 min to obtain solution A, and then 0.075 g of glycine was added to solution A, and the solution was placed on a magnetic heating stirrer and heated at 80 ° C and continued to stir for 15 min to obtain solution B, and solution B was placed in an oven at 80 ° C for 10 h to obtain a gel precursor C, and then the gel precursor C was placed in a muffle furnace and heated to 700 ° C in an air atmosphere to cause a combustion reaction, and then kept warm for 1 h to obtain a high entropy oxide material precursor D, and the high entropy oxide material precursor D was cooled to room temperature with the furnace to obtain a high entropy oxide material (Fe 0.2 Ni 0.2 Cu 0.2 Zn 0.2 Sn 0.2 )3O4.
[0042] Example 3
[0043] The method for preparing the high entropy oxide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0044] First, 0.404 g, 0.291 g, 0.242 g, 0.297 g, and 0.367 g (molar ratio of 1:1:1:1:1) of ferric nitrate nonahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, and tin nitrate were weighed and dissolved in 30 ml of anhydrous ethanol, and then placed on a magnetic stirrer and stirred for 15 min to obtain solution A, and then 0.075 g of glycine was added to solution A, and the solution was placed on a magnetic heating stirrer and heated at 80 ° C and continued to stir for 15 min to obtain solution B, and solution B was placed in an oven at 80 ° C for 10 h to obtain a gel precursor C, and then the gel precursor C was placed in a muffle furnace and heated to 800 ° C in an air atmosphere to generate a combustion reaction, and then kept warm for 1 h to obtain a high entropy oxide material precursor D, and the high entropy oxide material precursor D was cooled to room temperature with the furnace to obtain a high entropy oxide material (Fe 0.2 Ni 0.2 Cu 0.2 Zn 0.2 Sn 0.2 )3O4.
[0045] Example 4
[0046] The method for preparing the high entropy oxide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0047] First, 0.404 g, 0.291 g, 0.242 g, 0.297 g, and 0.367 g (molar ratio of 1:1:1:1:1) of ferric nitrate nonahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, and tin nitrate were weighed and dissolved in 30 ml of anhydrous ethanol, and then placed on a magnetic stirrer and stirred for 15 min to obtain solution A, and then 0.075 g of glycine was added to solution A, and the solution was placed on a magnetic heating stirrer and heated at 80 ° C and continued to stir for 15 min to obtain solution B, and solution B was placed in an oven at 80 ° C for 10 h to obtain a gel precursor C, and then the gel precursor C was placed in a muffle furnace and heated to 850 ° C in an air atmosphere to generate a combustion reaction, and then kept warm for 1 h to obtain a high entropy oxide material precursor D, and the high entropy oxide material precursor D was cooled to room temperature with the furnace to obtain a high entropy oxide material (Fe 0.2 Ni 0.2 Cu 0.2 Zn 0.2 Sn 0.2 )3O4.
[0048] Example 5
[0049] The method for preparing the high entropy oxide material for the negative electrode of a lithium ion battery in this embodiment comprises the following steps:
[0050] First, 0.404 g, 0.291 g, 0.242 g, 0.297 g, and 0.367 g (molar ratio of 1:1:1:1:1) of ferric nitrate nonahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, and tin nitrate were weighed and dissolved in 30 ml of anhydrous ethanol, and then placed on a magnetic stirrer and stirred for 15 min to obtain solution A, and then 0.075 g of glycine was added to solution A, and the solution was placed on a magnetic heating stirrer and heated at 80 ° C and continued to stir for 15 min to obtain solution B, and solution B was placed in an oven at 80 ° C for 10 h to obtain a gel precursor C, and then the gel precursor C was placed in a muffle furnace and heated to 900 ° C in an air atmosphere to generate a combustion reaction, and then kept warm for 1 h to obtain a high entropy oxide material precursor D, and the high entropy oxide material precursor D was cooled to room temperature with the furnace to obtain a high entropy oxide material (Fe 0.2 Ni 0.2 Cu 0.2 Zn 0.2 Sn 0.2 )3O4.
[0051] Example 6 XRD test
[0052] The material prepared in Example 1 was subjected to XRD test, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that all diffraction peaks belong to the face-centered cubic spinel crystal system, and the diffraction peaks at diffraction angles (2θ) of 18.10°, 29.78°, 35.06°, 36.68°, 42.61°, 46.65°, 52.85°, 56.33°, 61.84°, 65.01°, 70.13°, 73.12°, 74.11°, and 78° correspond to the FCC spinel structure, respectively. (PDF#01-074-2149) (111), (220), (311), (222), (400), (331), (422), (333), (440), (531), (620), (533), (622) and (444) crystal planes, no other impurity phases were found, indicating that the HEO is a single-phase solid solution structure with disordered composition, ordered structure and high crystallinity. This shows that the synthesized product meets the expected target.
[0053] Example 7 SEM test
[0054] The material prepared in Example 1 was subjected to SEM test, and the test results are as follows: Figure 4 and Figure 5 As shown. Figure 4 It can be seen that HEO powder is composed of many tiny spherical nanoparticles. Figure 4 and Figure 5It can be seen that the particle size is relatively uniform, the morphology is solid irregular, and the powder particle size is micro-nano level, which indicates that the material has a good specific surface area and excellent lithium storage capacity.
[0055] Example 8 Battery Performance Test
[0056] The product of Example 1 is used as an electrode material for lithium-ion batteries
[0057] (1) The material of Example 1 was mixed with the conductive agent Super P and PVDF in a mass ratio of 7:2:1, ground and mixed in a mortar, an appropriate amount of NMP was added and then coated on a copper foil, placed in a vacuum drying oven at 80° C. for 12 h, and rolled and cut into pieces to obtain a battery negative electrode sheet;
[0058] (2) Using metal lithium sheet as the counter electrode, a 2016-type button battery was made in a glove box filled with argon gas. The diaphragm was celgard2250, and the electrolyte was 1M LiPF6 / EC:DEC (volume ratio 1:1). The battery performance of the prepared 2016-type button battery was tested on the blue power test system. The electrochemical energy storage performance of the prepared lithium-ion battery was tested.
[0059] (3) The charge and discharge range is 0.01-3V, and the charge and discharge rates are 100mA / g, 200mA / g, 300mA / g, 500mA / g, and 1000mA / g. The electrochemical energy storage performance of the prepared lithium-ion battery is tested, such as Figure 2 and Figure 3 shown.
[0060] Depend on Figure 2 It can be seen that the high entropy oxide material (Fe 0.2 Ni 0.2 Cu 0.2 Zn 0.2 Sn 0.2 )3O4. At different charge and discharge current densities of 100mA / g, 200mA / g, 300mA / g, 500mA / g, and 1000mA / g, the discharge specific capacity is about 594mAh / g, 475.6mAh / g, 399mAh / g, 316.1mAh / g, and 225mAh / g, and the capacity retention rates are 97.22%, 97.93%, 98.48%, 98.68%, and 98.89%, respectively, indicating that the lithium-ion battery made of this material has good cycle performance and high coulombic efficiency.
[0061] Depend on Figure 3 It can be seen that the high entropy oxide material (Fe 0.2 Ni0.2 Cu 0.2 Zn 0.2 Sn 0.2 After 50 cycles of )3O4 at a current density of 100mA / g, its specific capacity is still about 444.4mAh / g, and the capacity retention rate is about 98.28%. This shows that the lithium-ion battery made of this material has good cycle performance and high coulombic efficiency.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A high entropy oxide material for a lithium ion battery negative electrode, characterized in that: The chemical formula of the high entropy oxide material is: (Fe 0.2 Ni 0.2 Cu 0.2 Zn 0.2 Sn 0.2 )3O4.
2. A method for preparing the high entropy oxide material for lithium ion battery negative electrode according to claim 1, characterized in that: The steps include: Step 1, weighing an iron source, a nickel source, a copper source, a zinc source, and a tin source, dissolving them in a solvent, placing them on a magnetic stirrer and stirring to obtain a solution A; Step 2: adding fuel to the solution A, heating and continuing to stir to obtain solution B; Step 3, drying the solution B to obtain a gel precursor C; Step 4: placing the gel precursor C in a muffle furnace to undergo a combustion reaction, and then keeping the temperature to obtain a high entropy oxide material precursor D; Step 5: Cooling the high entropy oxide material precursor D in the furnace to obtain a high entropy oxide material for a negative electrode of a lithium-ion battery.
3. The method for preparing a high entropy oxide material for a negative electrode of a lithium ion battery according to claim 2, characterized in that: The specific steps include: Step 1, weighing an iron source, a nickel source, a copper source, a zinc source, and a tin source, and dissolving them in anhydrous ethanol, and then placing them on a magnetic stirrer and stirring for 15 minutes to obtain a solution A; Step 2: adding a fuel in a stoichiometric ratio equal to the chemical reagent in step 1 to the solution A, placing the solution on a magnetic heating stirrer and heating at 80° C. and continuing to stir for 15 minutes to obtain a solution B; Step 3, placing the solution B in an oven at 80° C. to dry to obtain a gel precursor C; Step 4: placing the gel precursor C in a muffle furnace, heating it to 700-900° C. in an air atmosphere to cause a combustion reaction, and then keeping the temperature for 1 hour to obtain a high entropy oxide material precursor D; Step 5: Cooling the high entropy oxide material precursor D in the furnace to obtain a high entropy oxide material for a negative electrode of a lithium-ion battery.
4. The method for preparing a high entropy oxide material for a negative electrode of a lithium ion battery according to claim 2 or 3, characterized in that: In step 1, the iron source is ferric nitrate nonahydrate; the nickel source is nickel nitrate hexahydrate; the copper source is copper nitrate trihydrate; the zinc source is zinc nitrate hexahydrate; and the tin source is tin nitrate.
5. The method for preparing a high entropy oxide material for a negative electrode of a lithium ion battery according to claim 2 or 3, characterized in that: In step 1, the molar ratio of the iron source, nickel source, copper source, zinc source and tin source is 1:1:1:1:
1.
6. The method for preparing a high entropy oxide material for a negative electrode of a lithium ion battery according to claim 2 or 3, characterized in that: In step 2, the fuel is glycine.
7. A negative electrode material for a lithium ion battery, characterized in that: The high entropy oxide material for lithium-ion battery negative electrode according to claim 1 is mixed with the conductive agent Super P and PVDF in a mass ratio of 7:2:1, ground and mixed evenly in a mortar, added with an appropriate amount of NMP and then coated on a copper foil, placed in a vacuum drying oven at 80°C for 12 hours, and rolled and cut to obtain a battery negative electrode sheet.
8. A lithium ion battery, characterized in that: The invention comprises the battery negative electrode sheet as claimed in claim 7, and also comprises a battery casing, a positive electrode sheet, a separator and an electrolyte.
